Islas lingüísticas dentro del dominio español: El caso del vasco y del náhuatl - Petkova, Ingrid (Verbum – Analecta Neolatina, 2008)
Basque and Nahuatl are special in that they form certain kinds of islands in the Spanish-speaking world. Both languages differ fromSpanish: Basque is not an Indo-European language, its origin is unknown; Nahuatl belongs to the Uto-Aztec language family. Basque is an agglutinating, whereas Nahuatl is an incorporating language. Both live in a close coexistence with Spanish, which is one of the most common spoken languages in the world. In spite of this co-existence with the dominant Spanish language and culture for centuries, Basque- and Nahuatl-speaking minorities have preserved their identity and vitality. This paper intends to give a brief overview of Basque and Nahuatl, linguistic policy, as well as literature in these two languages.